Implementasi Permainan Tradisional pada Perancangan Desain Elemen Interior untuk Anak-Anak - Yiawla Ismarch Priadi (Intra, 2017)
The traditional games are diverse in each region, whether originating from the culture of the region it self or adopted from a culture outside the region but is played in Indonesian cultural ways and customs. However, as the times progresses rapidly, traditional games were increasingly abandoned. Seeing this phenomenon, a lot of effort has been made to raise the prestige of traditional games. With that fact, as a form of supporting the effort to preserve traditional games, the author developed the idea to implement traditional games, especially traditional games on interior elements for children. The object that will be designed is an interior product for children which besides serving to accommodate learning activities as well as a means of playing while learning through the implementation of traditional games on the interior elements. The formulation of the issues discussed is what traditional games can be implemented and what construction systems and materials are appropriate for children. The method used is design thinking method, by doing observation and field survey, interviewing, gathering related literature, programming analysis phase, design schematic stage, final design stage, and realization stage of 1: 1 prototype.